Performance of defensive shares on the JSE during financial crisis: evidence from analysis of returns and volatility - Arguile, Wayne Peter (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2012)
This study analyses whether historically defensive sectors on the JSE have "“ with respect to the market "“ proven to be defensive during the recent global financial crisis. By withstanding the shocks of market volatility, defensive industries (such as pharmaceuticals and consumer staples) are renowned for their consistent performance throughout the business cycle. Using daily data for the period 2000"“2009, the study compares the descriptive statistics of sector returns before and during the crisis. The volatility of each sector relative to the market index is calculated using the CAPM beta and a simplified volatility ratio. The same comparison is extended to the conditional volatilities of each of the sectors, which is estimated using the GARCH model and two of its extensions: the EGARCH and GJR GARCH models. While no sector experienced a positive mean return during the financial crisis, Healthcare, Consumer Goods, Consumer Services and Industrials all proved less volatile than the market. Surprisingly, Telecommunications proved more volatile than the market and experienced leverage effects during the financial crisis. Since the timing of a recession is difficult to predict, defensive securities were found to be a useful investment tool for protection against adverse movements in the stock market.
Keywords: Industries -- South Africa -- Finance; Industries -- South Africa -- Statistics; Johannesburg Stock Exchange; Rational expectations (Economic theory)